The First Step of Health Policy-Making for Lifestyle Modifications at Middle Age: Problem Identification in 40- to 60-Year-Old Population, Northern Iran - Simin Mouodi; Seyed Reza Hosseini; Reza Ghadimi; Ali Bijani; Robert Graham Cumming; Hassan Ashrafian Amiri; Fatemeh Bayani; Shima Sum (Hindawi Limited, 2018)
Background. The purpose of this study was to determine the current situation of lifestyle behaviors and related outcomes, as the first step to make proper local health policies for improvement of health lifestyle behaviors. Materials and Methods. This analytic research has been conducted as a cross-sectional study on the middle-aged (40-60 years old) population of Amirkola, Northern Iran. The Persian translation of the Health-Promoting Lifestyle Profile II questionnaire and the International Physical Activity Questionnaire were used for data collection. Also, anthropometric variables, blood pressure, fasting blood sugar, and serum lipids profile were examined. Results. Three hundred one individuals have been enrolled in the study. Results showed that 10.6% of the participants had unhealthy lifestyle behaviors in the subdomain of spiritual growth; 46.8% in the subdomain of health responsibility; and 48.2% in the subdomains of stress management, physical activity, and nutrition; men had more physical activity than women (p<0.001). Totally, 189 persons (63.9%) had serum cholesterol greater than or equal to 200 mg/dL; seventy-five individuals (25%) had high blood pressure. One hundred twenty-six persons (81.8%) of women and 103 (70.1%) of men were overweight or obese. Conclusions. Health lifestyle behaviors in 40- to 60-year-old population need a proper intervention to improve the current situation.